Relação entre doença de alzheimer e insônia: uma revisão bibliográfica - Barros, Maria Beatriz Abath Aires de (2021)
Introduction: Alzheimer's disease is the most common type of dementia in the elderly population, with well-defined clinical and pathological presentation, affecting at least 5% of individuals over 65 years of age and 20% of those over 85 years of age. Among the prevalent neuropsychiatric symptoms, sleep disorders are highly relevant and they correlate with the development of this type of dementia if present during adulthood. Objectives: The present study aimed to assess the prevalence of sleep disorders and Alzheimer's disease, as well as the relationship between insomnia during adulthood and the appearance of this type of dementia. Materials and Methods: This was a literature review study classified as cross-sectional, observational, descriptive and quantitative. LILACS, PubMed, Scielo and MEDLINE were used as data source to search for articles in Portuguese and English. For the collection and analysis of the data, the method validated by Ursi (2005) was used, which includes: identification of the original article, institution hosting the study, type of publication, methodological characteristics of the study and evaluation of methodological rigor. The data obtained were analyzed and a descriptive review was carried out on the results of the selected publications, in order to assess the relationship between Alzheimer's disease and insomnia. Results: 334 publications were found. After applying the selection criteria, 21 articles remained in the sample and had their information collected for analysis. The studies analyzed were in agreement on the positive relationship between insomnia and Alzheimer's disease, in which the prevalence of sleep disorders varies from 14% to 69%. It has a well-defined pathophysiology, in which, since the preclinical stage of the disease, changes in amyloid deposits related to poor sleep quality have already occurred, which generates fragmentation of the sleep-wake cycle. In addition, low sleep efficiency leads to lower frontal brain volume. Changes in the frontal, parietal and frontal regions are related to a greater vulnerability to age-related changes and this type of dementia, and may be responsible for cognitive deficits that coexist with sleep disorders. Conclusion: Bibliographic research has shown that patients with an established diagnosis of Alzheimer's disease are highly likely to manifest sleep disorders, as one of the psychological behavioral symptoms of dementia. In addition, adults who suffer from insomnia have wellestablished anatomopathological and physiological changes, which over time increase the chance of developing Alzheimer's disease.